Therapeutic role of Crateva religiosa in diabetic nephropathy: Insights into key signaling pathways - Muhammad Ali; Hafiz M. Irfan; Alamgeer; Aman Ullah; Magda H. Abdellattif; Mahmoud Elodemi; Mohammad Zubair; Ajmal Khan; Ahmed Al-Harrasi (PLoS ONE, 2025)
Crateva religiosa, a plant used in traditional medicine, is valued for its bioactive properties. Traditional approaches are more accepted worldwide as a cost effective alternatives being used in network pharmacology to explore the complex interactions of drug targets among molecular pathways. The study investigated the potential of Crateva religiosa’s phytoconstituents using meticulous computational analysis and empirical confirmation. The IMPPAT, GeneCards and DisGeNET data bases were used to obtain the active moieties and disease targets respectively. Crateva phytoconstituent’s DN-target network and protein-protein interaction (PPI) network were developed and analyzed using the STRING online platform and Cytoscape software. GO and KEGG analyses were conducted using the g: profiler databases while the process of molecular docking involved the use of MOE software. The screening process identified dillapiole (CR-C1), beta ionone (CR-C2) 10-epi-γ-eudesmol (CR-C3), cis/trans linalool oxide (CR-C4/5) and nerolidol (CR-C6), as potential active phytoconstituents of C. religiosa and AKT1, PPARG, PTGS2, EGFR, ESR1, JAK2, MAPK1, PARP1, GSK3B, and PPARA as matching targets in DN. The enrichment analysis revealed that the common targets were primarily linked to inflammatory response, oxidative stress, immunological modulation, and cell death. The main signal pathways suggested were PI3K-Akt, AGE-RAGE, and IL-17. Moreover, molecular docking analysis determined that the AKT1, PPARG and PTGS2 are the essential targets that had a good affinity for their respective active molecules.